Single Dose of Consensus Hemagglutinin-Based Virus-Like Particles Vaccine Protects Chickens against Divergent H5 Subtype Influenza Viruses - Wu, Peipei; Lu, Jihu; Zhang, Xuehua; Mei, Mei; Feng, Lei; Peng, Daxin; Hou, Jibo; Kang, Sang-Moo; Liu, Xiufan; Tang, Yinghua (Frontiers in Immunology, 2017)
The H5 subtype highly pathogenic avian influenza (HPAI) virus is one of the greatest threats to global poultry industry. To develop broadly protective H5 subunit vaccine, a recombinant consensus HA sequence (rHA) was constructed and expressed in virus-like particles (rHA VLPs) in the baculovirus-insect cell system. The efficacy of the rHA VLPs vaccine with or without immunopotentiator (CVCVA5) was assessed in chickens. Compared to the commercial Re6 or Re6-CVCVA5 vaccines, single dose immunization of chickens with rHA VLPs or rHA-CVCVA5 vaccines induced higher levels of serum hemmaglutinin inhibition titers and neutralization titers, mucosal antibodies, IFN-γ and IL-4 cytokines in sera, and cytotoxic T lymphocyte responses. The rHA VLPs vaccine was superior to the commercial Re6 vaccine in conferring cross-protection against different clades of H5 subtype viruses. This study reports that H5 subtype consensus-HA VLP single dose vaccination provides broad protection against HPAI virus in chickens.